Created in the image of God and sexuality in early-Jewish writings - Eck, Ernest Van (HTS teologiese studies, 2017)
This article pays tribute to the contribution made by Yolanda Dreyer regarding critique on the prevalence of patriarchy in society, as well as her defence of homosexuality as a normal sexual orientation. Taking as point of departure her work on the woman as created in God’s image, it is argued that understanding the metaphor ‘created in God’s image’ as referring to rule over all, and not as created as man and woman, has important implications for the relationship between man and woman, as well as the normalisation of relationships between the same sex.